Metabolic profile elucidation of Zhi–Zi–Da–Huang decoction in rat intestinal bacteria using high-resolution mass spectrometry combined with multiple analytical perspectives. (2nd January 2019) - Wang, Miao; Hu, Qing; Shi, Qingshui; Yang, Gongjun; Feng, Fang
Abstract: 1. Zhi–Zi–Da–Huang decoction (ZZDHD) has been widely used for the treatment of alcoholic jaundice, alcoholic liver disease, and acute hepatitis in China for thousands of years. Conventionally decoctions are administered orally, after which the metabolism caused by the enzymes in intestinal bacteria may influence significantly on the curative effects or toxicity. 2. In this work, the comprehensive metabolic process of ZZDHD in intestinal bacteria was investigated reliably using high-resolution HPLC-DAD-ESI-TOF/MS. Besides, a novel strategy for major-to-trace metabolites identification which integrated information derived from diagnostic fragment ions, mass spectral similarity filter strategy, dynamic metabolic change of target compounds and relevant behavior in LC-MS was adopted. 3. As a result, 45 compounds, including 26 bio-converted prototypes and 19 newly generated metabolites were detected and tentatively identified. The metabolic profile of ZZDHD in gastro-intestinal was subsequently elucidated. Deglycosylation, oxidation, reduction, acetylation, and ring cleavage were all observed in the biotransformation of the decoction. Among the rest, deglycosylation was found to be the predominant metabolic pathway. 4. The results obtained herein provided a practical strategy for metabolic profile elucidation of traditional herbal medicines. Moreover, it would be helpful to unravel how the oral decoctions play the therapeutic role in vivo .